Impact of direct-acting antiviral treatment on time and out-of-pocket costs for hepatitis C patients - Yasmin A Saeed; Arcturus Phoon; Josephine F Wong; Kate Mason; Seff Pinch; Valérie Martel-Laferrière; Julie Bruneau; Jordan J Feld; Zeny Feng; Samuel S Lee; Jeff Powis; Beate Sander; et al. (Canadian Liver Journal, 2026)
Abstract Background: Direct-acting antiviral (DAA) therapies have transformed care for chronic hepatitis C (CHC); however, the effect of DAA therapy on patient-borne costs is unclear. These costs can pose a substantial burden for patients and their families—even in a publicly funded health system. We estimated the patient-borne costs associated with CHC and the impact of DAA therapy on these costs. Methods: We recruited patients with CHC who were prescribed DAA therapy at two specialized liver clinics and five low-barrier community clinics in Calgary, Montreal, and Toronto, Canada. We interviewed patients before and 1 year after treatment with DAAs. We administered a costs questionnaire eliciting patient-borne health care–associated costs and time costs for the previous 3 months. Results: One hundred and one patients completed the costs questionnaire before and 1 year after DAA treatment. Most (59%) were male, with an average age of 54 years. Ninety-five percent achieved a sustained virologic response (SVR) during the study. Patients spent an average of 41.3 hours attending health care appointments in the 3 months preceding their baseline questionnaire, compared with 14.9 hours at 1 year post-treatment. Valued at average 2020 Canadian wages (CAD$30.03/hour), this represented time costs of CAD$1,240 at baseline and CAD$449 post-treatment. Out-of-pocket health care costs for the previous 3 months averaged CAD$115 at baseline and CAD$43 at 1 year post-treatment. Conclusions: Our study suggests that patient-borne costs are substantially lower after DAA therapy. These costs may pose a significant burden for patients with CHC and should be incorporated into cost-effectiveness analyses of hepatitis C screening and treatment programs.